YBX1 alleviates ferroptosis in osteoporosis via the ATF4/FSP1 axis in an m5C manner - Lei Tong; Yanbo Chen; Yan Gao; Xiaoming Gao; Yanming Hao (Journal of Orthopaedic Surgery and Research)
Abstract Background Interactions between RNA-binding proteins and RNA regulate RNA transcription during osteoporosis. Ferroptosis, a programmed cell death caused by iron metabolism, plays a vital role in osteoporosis. However, the mechanisms by which RNA-binding proteins are involved in ferroptosis during osteoporosis remain unclear. Methods We established an in vitro model of osteoporosis induced by D-galactose (D-gal) in MC3T3-E1 cells. Ferroptosis suppressor protein 1 (FSP1), activating transcription factor 4 (ATF4), and Y-box binding protein 1 (YBX1) knockdown MC3T3-E1 cells were generated, and their effects on ferroptosis were verified by measuring lipid reactive oxygen species levels and cellular Fe2+. Chromatin immunoprecipitation and luciferase assays were performed to confirm the binding of ATF4 to the FSP1 promoter. RNA pulldown and RNA immunoprecipitation experiments were used to determine the binding between YBX1 and ATF4 mRNA and to test the effect of YBX1 on ATF4 mRNA stability in a 5-methylcytosine (m5C)-dependent manner. Results FSP1 or YBX1 knockdown led to a D-gal-induced increase in lipid reactive oxygen species levels and cellular Fe2+ in MC3T3-E1 cells, which was alleviated by ATF4 overexpression. ATF4 inhibits ferroptosis by binding to the FSP1 promoter. In addition, YBX1 increased ATF4 mRNA stability through m5C RNA modification and inhibited ferroptosis in MC3T3-E1 cells via the ATF4/FSP1 axis. Conclusion Our results showed that YBX1 could alleviate ferroptosis via the ATF4/FSP1 axis in an m5C-dependent manner in D-gal-induced osteoblasts, suggesting that YBX1 may be a new target for osteoporosis treatment. Graphical Abstract